2021
DOI: 10.1186/s13287-021-02640-y
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3/NLRP3 signaling in the mesenchymal stromal niche regulates myeloid-biased hematopoiesis

Abstract: Background The fate of hematopoietic stem cells (HSCs) is determined by a complex regulatory network that includes both intrinsic and extrinsic signals. In the past decades, many intrinsic key molecules of HSCs have been shown to control hematopoiesis homeostasis. Non-hematopoietic niche cells also contribute to the self-renewal, quiescence, and differentiation of HSCs. Mesenchymal stromal cells (MSCs) have been identified as important components of the niche. However, the regulatory role of MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…A plethora of supportive factors are provided in the niches (Table 1). Recent evidence showed that the key niche factors SCF and CXCL12 can be modulated by the Caspase3/NLRP3 signaling, which extends understanding of regulatory mechanisms influencing haematopoiesis (40). Of note, the same molecular cue presented by diverse cells in BM niches may serve different functions in each compartment.…”
Section: Composition Of Bm Nichesmentioning
confidence: 80%
“…A plethora of supportive factors are provided in the niches (Table 1). Recent evidence showed that the key niche factors SCF and CXCL12 can be modulated by the Caspase3/NLRP3 signaling, which extends understanding of regulatory mechanisms influencing haematopoiesis (40). Of note, the same molecular cue presented by diverse cells in BM niches may serve different functions in each compartment.…”
Section: Composition Of Bm Nichesmentioning
confidence: 80%
“…The NLRP3 inflammasome pathway belongs to the classical inflammasome pyroptosis pathway (Caspase-1 mediated). In addition, there are non-classical inflammasome pyroptosis pathways (Caspase-4, Caspase-5, Caspase-11 mediated) and apoptotic protein Caspase-3 mediated pyroptosis pathway ( Moretti et al, 2022 ; Fu et al, 2021 ; Zhang et al, 2021b ). The role of NLRP3 inflammasome for synovitis in KOA is a hot topic in recent years, many studies have shown that NLRP3 inflammasome is a potential mechanism of synovitis in KOA, but it needs to be further studied.…”
Section: The Structure and Function Of Nlrp3 Inflammasomementioning
confidence: 99%
“…The chemotherapy-caused injury of MSCs affects immune reconstitution and hematopoietic function recovery of donor HSCs in the host hematopoietic microenvironment after HSC transplantation [ 20 ]. Bone-associated mesenchymal stem cells (BA-MSCs), which are derived from the endosteum, are an essential component for the formation and maintenance of the hematopoietic microenvironment and play an important role in the regulation and support of hematopoietic activity [ 21 , 22 ]. Therefore, an in-depth study of the mechanism of BA-MSC injury caused by chemotherapy is crucial to improve the success rate of clinical HSC transplantation, promote immune reconstitution, and reduce the risk of postoperative infection.…”
Section: Introductionmentioning
confidence: 99%